2020
DOI: 10.1021/acscatal.0c04722
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Role Catalysis by Thiobenzoic Acid in Cα–H Arylation under Photoirradiation

Abstract: Thiobenzoic acid (TBA) can serve as a single-electron reducing agent under photoirradiation from a blue light-emitting diode, in the presence of appropriate electron acceptors, and the resulting sulfur-centered radical species undergoes hydrogen atom abstraction. This dual-role catalysis by TBA enables regioselectivie Cα−H arylation of benzylamines, benzyl alcohols, and ethers, as well as dihydroimidazoles, with cyano(hetero)arenes in good yield, without the need for a transition-metal photocatalyst and/or syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 70 publications
0
38
0
1
Order By: Relevance
“…have shown that the excited state of a thiobenzoate anion could be engaged in the catalytic single-electron reduction of cyanoarenes (Scheme ). By leveraging the dual role of the thiobenzoate anion catalyst, namely a one-electron reducing catalyst and as HAT catalyst, this method allowed the direct benzylic Csp 3 –H arylation with cyanoarenes in the presence of a catalytic amount (20 mol %) of thiobenzoic acid under blue-light irradiation. The proposed mechanism of this transformation starts with deprotonation of XXI by base to produce thiobenzoate XXII , which could be excited by visible light.…”
Section: Light-induced Thiolate Catalysis Enabled By the Excited Stat...mentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that the excited state of a thiobenzoate anion could be engaged in the catalytic single-electron reduction of cyanoarenes (Scheme ). By leveraging the dual role of the thiobenzoate anion catalyst, namely a one-electron reducing catalyst and as HAT catalyst, this method allowed the direct benzylic Csp 3 –H arylation with cyanoarenes in the presence of a catalytic amount (20 mol %) of thiobenzoic acid under blue-light irradiation. The proposed mechanism of this transformation starts with deprotonation of XXI by base to produce thiobenzoate XXII , which could be excited by visible light.…”
Section: Light-induced Thiolate Catalysis Enabled By the Excited Stat...mentioning
confidence: 99%
“…Recently, Hamashima et al have shown that the excited state of a thiobenzoate anion could be engaged in the catalytic single-electron reduction of cyanoarenes (Scheme 12). 48 By leveraging the dual role of the thiobenzoate anion catalyst, namely a one-electron reducing catalyst and as HAT catalyst, this method allowed the direct benzylic Csp hydrogen atom from the substrate to give a carbon radical XXV, simultaneously regenerating the catalyst XXI. Further radical−radical coupling between XXIII and XXV affords the target product after releasing the cyanide anion.…”
Section: Light-induced Thiolate Catalysis Enabledmentioning
confidence: 99%
“…For example, Hamashima recently reported photoinduced C–H arylation of benzyl amine 72 with 1,4-dicyanobenzene 73 in the presence of commercially available thiobenzoic acid ( 74 ) as a catalyst to produce diarylmethylamine 75 ( Scheme 10 ). 38 In this process, the photoexcited benzothioate ion 76* undergoes SET reduction of 1,4-dicyanobenzene 73 ( E red = –1.64 V vs SCE) 39 to generate a persistent anion radical of 1,4-dicyanobenzene 77 . The simultaneously formed thiyl radical 78 induces HAT from benzyl amine 72 to form the transient benzylic radical 79 , which could be coupled with the anion radical 77 to liberate the C–H arylated product 75 .…”
Section: Sulfur Anions As Photoredox and Hydrogen Atom Transfer Catalystsmentioning
confidence: 99%
“…Template for SYNLETT Thieme Hamashima and co-workers later on discovered that the same -amino C(sp 3 )−H arylation of benzylamines can be achieved without any exogenous photocatalyst by realising the photocatalytic activity of thiobenzoic acid (TBA) (Figure 5). 23 Photoexcitation of the conjugate base 5a of TBA leads to SET with the electron-deficient arene partner to give radical anion 5e and sulfur centered radical 5b. Species 5b then engages in regioselective HAT with a benzylic -amino C(sp 3 )−H bond and the mechanism otherwise follows that in Template for SYNLETT Thieme steric hindrance and follows a Curtin-Hammett principle (Figure 6).…”
Section: Accepted Manuscriptmentioning
confidence: 99%